The landscape and clinical impact of tumor-associated macrophages and PD-L1 in primary breast cancers and their brain metastases - Zimmer, Yannik Nicola; Hanke, Benjamin; Neyazi, Belal; Rashidi, Ali; Schaufler, Anna; Dumitru, Claudia Alexandra; Ignatov, Atanas; Mawrin, Christian; Sandalcioglu, I. Erol; Stein, Klaus-Peter (Frontiers in Immunology, 2025)
BackgroundTumor-associated macrophages (TAMs) influence the tumor microenvironment and can contribute to tumor progression. They can polarize into M1 (classically activated) or M2 (alternatively activated) phenotype, which exhibit divergent functional characteristics. The comparison of TAMs between primary breast cancer (BC) and corresponding brain metastases (BMs) remains insufficiently explored and is the focus of this study.MethodsThis study aimed to compare the infiltration of TAMs and PD-L1 expression in primary breast cancer and their brain metastases, by analyzing 27 paired samples and 26 additional brain metastases. Immunohistochemical staining was performed for the following markers: CD68, CD86 (M1), CD163 (M2), and PD-L1.ResultsCD68 showed significantly higher expression levels in brain metastases compared to the corresponding primary breast cancers. In contrast, the expression of CD86 and CD163 showed comparable results between the primary tumors and their brain metastatic counterparts. Macrophages were consistently found to be more frequently present in the tumor stroma compared to the tumor nest. Survival analysis of the primary revealed that high expression of CD163 was associated with a recurrence-free survival. (RFS). Conversely, high expression of CD86 in brain metastases was associated with longer overall survival. Low expression of CD68 and CD163 in brain metastases correlated with the presence of meningeal carcinomatosis. The expression of PD-L1 in the primary tumor did not necessarily reflect the status of PD-L1 in the corresponding brain metastases.ConclusionsOverall, this study highlights the complex influence of TAMs on the course of primary breast cancers and their brain metastases. The discordant expression of the immune checkpoint molecule PD-L1 underscores the importance of evaluating the PD-L1 status in cerebral metastases to guide potential immunotherapeutic approaches.